A longitudinal perspective on the associations between work engagement and workaholism. Issue 1 (2nd January 2021) - Tóth-Király, István; Morin, Alexandre J. S.; Salmela-Aro, Katariina
ABSTRACT: The purpose of this two-wave longitudinal study was to examine the associations between work engagement and workaholism to better understand the psychological mechanisms underpinning high levels of work investment. These associations were examined in a sample of 514 employees using latent change models, allowing us to obtain a direct and explicit estimate of change occurring in both constructs over a 3-year period. These analyses relied on a bifactor representation of work engagement and workaholism, allowing us to properly disaggregate the global and specific levels of both constructs in the estimation of these longitudinal associations. To further enrich our theoretical understanding of the mechanisms at play in these relations, we also considered associations between these two constructs and employees' levels of harmonious and obsessive work passion, two other facets of heavy work investment. Our results revealed the longitudinal independence of employees' global levels work engagement and workaholism, showing that longitudinal associations between these two constructs occurred at the specific, rather than global, level. Harmonious work passion was only found to be associated to global and specific components of work engagement, whereas obsessive work passion was found to be associated with global and specific components of both work engagement and workaholism.